Implementasi Penegakan Hukum atas Pelanggaran Lalu Lintas Berbasis ETLE di Wilayah Jawa Timur - Oktavio Siwi Nagari; Juli Nurani (Fakultas Hukum Universitas Bhayangkara Surabaya, 2026)
Traffic violations remain a serious challenge in East Java, the region with the highest violation rate in Indonesia. This study aims to analyze the legal basis for traffic violation enforcement using Electronic Traffic Law Enforcement (ETLE) as well as legal protections for road users in the region, using a normative legal research method. The results of the study indicate that the ETLE system is supported by a robust regulatory framework, including Law No. 22 of 2009 on Road Traffic and Transportation, Government Regulation No. 80 of 2012, and National Police Regulation No. 2 of 2025, which collectively provide legal certainty for law enforcement officials and the general public. Legal protection for road users is realized through the objectivity of electronic evidence, the mechanism for sending confirmation letters to violators, and the transparency of online fine payments. Nevertheless, several challenges remain, including the uneven distribution of camera infrastructure across various regions, weak data synchronization among relevant agencies, and the lack of an explicit appeal mechanism for members of the public who feel aggrieved. Using Lawrence M. Friedman’s legal system theory, these challenges reflect weaknesses in the components of legal structure and legal culture that need to be systematically strengthened to achieve effective, transparent, and fair traffic law enforcement.